The Biopsychosocial Model and Perinatal Health Care: Determinants of Perinatal Care in a Community Sample - Duberstein, Zoe T.; Brunner, Jessica; Panisch, Lisa S.; Bandyopadhyay, Sanjukta; Irvine, Carrie; Macri, Jenna A.; Pressman, Eva; Thornburg, Loralei L.; Poleshuck, Ellen; Bell, Keisha; Best, Meghan; Barrett, Emily; et al. (Frontiers in Psychiatry, 2021)
Insufficient care in the perinatal period is associated with poorer maternal health, poorer perinatal outcomes, infant mortality, and health inequalities. Identifying the sources of and reducing the rates of insufficient care is therefore a major clinical and public health objective. We propose a specific application of the biopsychosocial model that conceptualizes prenatal and postpartum care quality as health markers that are influenced by psychological factors and family and social context. Clinic attendance data were abstracted from the electronic medical records of N = 291 participants enrolled in a longitudinal pregnancy cohort study of healthy women who have been followed since the first trimester; the Kotelchuck Index (KI) was calculated as an index of perinatal care utilization. Detailed prenatal psychological, social, and sociodemographic data were collected from self-report questionnaire and interview. Bivariate analyses indicated socio-demographic (e.g., race), psychological (e.g., response to perceived racism, affective symptoms, trauma experience), and social and family context (e.g., social support, family size) significantly influenced pre- and post-natal care utilization. Multivariate logistic regression analyses, adjusting for medical complications, identified social and family context as robust predictors of perinatal care utilization. The findings underscore the need for biopsychosocial models of health care and highlight several potential strategies for improving health care utilization.